Analisis Dampak Permainan Daring Mobile Legend Terhadap Siswa Sekolah - Rafi Arya Putra; Fahrizal Ananda Putra (Yayasan Citra Dharma Cindekia, 2025)
Rapid advancements in information technology have led to the creation of new products that facilitate daily activities—devices such as televisions, computers, laptops, and mobile phones, along with internet access, have become commonplace. Today, many people own these information technology products. Developments in online gaming are attracting enthusiasts from diverse demographics, ranging from older adults and young people to elementary school-aged children. *Mobile Legends* is one of the most popular online games in Indonesia; it represents a form of electronic technology that has evolved rapidly over time amidst the current era of globalization. Playing *Mobile Legends* has both positive and negative effects. Positive impacts include making new friends and improving English language skills. Conversely, negative effects can include health issues, eye strain, neglecting study time, addiction, and a decline in academic performance—an important consideration given that education is a vital legacy passed down within the family.